Student’s intention and perception towards pursuing advanced accounting program / Anis Barieyah Mat Bahari, Wan Mardyatul Miza Wan Tahir and Nurhazrina Mat Rahim - Mat Bahari, Anis Barieyah; Wan Tahir, Wan Mardyatul Miza; Mat Rahim, Nurhazrina (Universiti Teknologi MARA Cawangan Pahang, 2014)
Professional accountants also known as Chartered Accountants and/or Malaysia Institute of Accountant (MIA) members must at least hold a bachelor’s degree from a local university or have passed a professional examination and become a member of a professional body. However, Bumiputra graduates in accounting advanced programs have decreased over the years. This paper aims to identify the factors influencing Malay accounting diploma students to pursue studies in bachelor degree programs or to sit for professional qualification examination in accountancy. In addition, the paper also examines the relationship between students’ perception and their intention to pursue bachelor and professional accounting programs. Questionnaires have been developed and distributed among students of Diploma of Accountancy from Universiti Teknologi MARA (UiTM). The findings show that 81% of the respondents intend to pursue a degree in accountancy, while the remaining believes that this program is too difficult. In addition, majority of the respondents have the intention to enroll in professional programs. Most of them favour Association of Chartered Certified Accountants (ACCA), due to the job opportunities available for the certified members. This study provides evidence of the significant influence of students’ perception towards their intention in pursuing higher level education in accounting programs.